Pulmonary atresia and intact ventricular septum and corrected transposition of the great arteries. - Shimizu, T (1981)
We report an 82-day-old infant with a rare combination of anomalies: pulmonary atresia associated with corrected transposition of the great arteries and intact ventricular septum; this is the second such recorded case. By using echocardiography, chest radiography, and electrocardiography the correct anatomical diagnosis was obtained before invasive investigation and necropsy.